Urethral Strictures and its Management at Tertiary Hospital of Nepal - Tiwari, Kabir; Upadhaya, Amit Mani; Kunwar, Ashok; Shrestha, Sanjesh Bhakta (Journal of Nepal Health Research Council, 2020)
Background: Urethral stricture can occur from urethral meatus to bladder neck. Treatment of urethral stricture include dilatation, endoscopic incision and anastomotic urethroplasty. The aim of this study is to report our experience in the management of different types of urethral strictures. Methods: We retrospectively reviewed the chart of all the patients of urethral stricture who received treatment at Kathmandu model hospital between January 2015 and October 2019. Different types of urethral stricture along with various modalities of treatment given were recorded. Results: Fifty patients were included in this study, all were males. Mean age was 49 (16-82) years. Bulbar urethra was the most common site in 54% of cases and bulbomembranous least common, only 10% of cases. Depending on sites and size of stricture, different types of surgery performed were meatoplasty, dviu and anastomotic urethroplasty. Conclusions: Urethral stricture is a troublesome disease and can occur anywhere from meatus to the bladder neck. Different surgical techniques are present and the treatment should be individualized, depending on location and length of the stricture. Keywords: Urethra; urethral stricture; urethroplasty